Testing the Pathogenic Potential of Cryphonectria parasitica and Related Species on Three Common European Fagaceae - Dennert, Francesca; Rigling, Daniel; Meyer, Joana B.; Schefer, Christopher; Augustiny, Eva; Prospero, Simone (Frontiers in Forests and Global Change, 2020)
Invasions by non-native pathogens represent a major threat to managed and natural ecosystems worldwide. Although necessary for adopting preventive strategies, the identification of invasive species before they are introduced is particularly difficult. Indeed, most pathogenic species that have become established in the last decades were first described only after they became invasive. To prevent further biological invasions, not only the early identification of potential new invasive plant pathogens is crucial, but also the assessment of their potential host range. In this study, we determined the pathogenicity and the saprotrophic ability of three Cryphonectria species towards three potential hosts in the family Fagaceae. For this, seedlings and dormant stems of European chestnut (Castanea sativa), pedunculate oak (Quercus robur) and European beech (Fagus sylvatica) were inoculated with different genotypes of C. parasitica (Asian species, invasive in Europe), C. naterciae (European species), and C. japonica (Asian species, not present in Europe). Lesion growth was measured and mortality assessed for four months. The highest damage was caused by C. parasitica on European chestnut, while C. japonica and C. naterciae induced significantly smaller lesions on this host species. All three Cryphonectria species did not grow saprophytically on F. sylvatica and Q. robur, but successfully colonized dormant stems of C. sativa. In the context of biological invasions, our study shows that the Asian C. japonica most likely represents a much less severe threat than C. parasitica for the tested European host species. Nonetheless, the ability of C. naterciae and C. japonica to saprotrophically colonize fresh chestnut wood may suggest that they could become established in chestnut forests and eventually infect weakened chestnut trees or other hosts not tested in this study.